Comparison of 7 Published LC-MS/MS Methods for the Simultaneous Measurement of Testosterone, Androstenedione, and Dehydroepiandrosterone in Serum. (6th January 2020) - Büttler, Rahel M; Martens, Frans; Fanelli, Flaminia; Pham, Hai T; Kushnir, Mark M; Janssen, Marcel J W; Owen, Laura; Taylor, Angela E; Soeborg, Tue; Blankenstein, Marinus A; Heijboer, Annemieke C
Abstract: BACKGROUND: Recently, LC-MS/MS was stated to be the method of choice to measure sex steroids. Because information on the mutual agreement of LC-MS/MS methods is scarce, we compared 7 published LC-MS/MS methods for the simultaneous measurement of testosterone, androstenedione, and dehydroepiandrosterone (DHEA). METHODS: We used 7 published LC-MS/MS methods to analyze in duplicate 55 random samples from both men and women. We performed Passing–Bablok regression analysis and calculated Pearson correlation coefficients to assess the agreement of the methods investigated with the median concentration measured by all methods, and we calculated the intraassay CV of each method derived from duplicate results and the CVs between the methods. RESULTS: Median concentrations of testosterone were 0.22–1.36 nmol/L for women and 8.27–27.98 nmol/L for men. Androstenedione and DHEA concentrations were 0.05–5.53 and 0.58–18.04 nmol/L, respectively. Intraassay CVs were 2.9%–10%, 1.2%–8.8%, 2.7%–13%, and 4.3%–16% for testosterone in women, testosterone in men, androstenedione, and DHEA. Slopes of the regression lines calculated by Passing–Bablok regression analysis were 0.92–1.08, 0.92–1.08, 0.90–1.13, and 0.91–1.41 for all testosterone values, testosterone in women, androstenedione, and DHEA. Intermethod CVs were 14%, 8%, 30%, and 22% for testosterone in women, testosterone in men, androstenedione, and DHEA. CONCLUSIONS: In general, the LC-MS/MS methods investigated show reasonable agreement. However, some of the assays show differences in standardization, and others show high variation.